1985
DOI: 10.1161/01.hyp.7.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Captopril potentiates chronotropic baroreflex responses to carotid stimuli in humans.

Abstract: Angiotensin II is a potent vasoconstrictor and has profound effects on autonomic neural mechanisms in experimental animals. Human carotid baroreflex control of arterial pressure and heart period was examined before and after acutely decreasing angiotensin II levels by administering 50 mg of oral captopril, an angiotensin converting enzyme inhibitor. Carotid baroreceptor stimuli were delivered by a neck chamber worn by 14 normotensive volunteers. Four subjects received placebo. Arterial pressure responses to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Diuretics, angiotensin-converting enzyme inhibitors and calcium channel antagonists lower BP equally well, but they do not appear to increase baroreflex sensitivity consistently. 2,[15][16][17][18][19][20][21][22] For example, in previous reports, captopril increased Figure 2 Absence of relationship between changes in arterial baroreflex sensitivity for heart rate (Log (BRS)) and changes in the variability of ambulatory awake arterial blood pressure (n = 34, r = −0.08, P Ͼ 0.6).…”
Section: Figurementioning
confidence: 80%
See 1 more Smart Citation
“…Diuretics, angiotensin-converting enzyme inhibitors and calcium channel antagonists lower BP equally well, but they do not appear to increase baroreflex sensitivity consistently. 2,[15][16][17][18][19][20][21][22] For example, in previous reports, captopril increased Figure 2 Absence of relationship between changes in arterial baroreflex sensitivity for heart rate (Log (BRS)) and changes in the variability of ambulatory awake arterial blood pressure (n = 34, r = −0.08, P Ͼ 0.6).…”
Section: Figurementioning
confidence: 80%
“…baroreflex sensitivity in normotensive and hypertensive humans, 15,16 and lisinopril in elderly hypertensives, 17 whereas ramipril, in a dose therapeutically equal to metoprolol, had no such effect. 2 There are conflicting reports on the effects of calcium channel antagonists on baroreflex sensitivity.…”
Section: Figurementioning
confidence: 96%
“…Angiotensin II can influence cardiovascular control mechanisms in man (50) and alter responses to AVP infusion in rats (35). Therefore, captopril was given to prevent changes in plasma angiotensin II which may have occurred during AVP infusion or lbnp exposure.…”
Section: Methodsmentioning
confidence: 99%
“…31 This author suggested that captopril potentiates reflex-mediated bradycardia via a reduction in central nervous system angiotensin II levels, which augments vagal responses to carotid baroreceptor stimuli. Since ANF has been reported to antagonize some of the vascular, 16 adrenal 432 " 34 and central nervous system 35 effects of angiotensin n, it also seems possible that the ANF-induced enhancement in vagal tone might somehow be related to functional antagonism of angiotensin II central effects.…”
Section: Figure 4 Reflex Chronotropic Responses (A//pj (Mean ± Sem) mentioning
confidence: 99%